Tajdidun Nikah as a Mechanism for Reconciliation and Strengthening Marital Commitment in Muslim Families - Muhammadong, Muhammadong (Samudra Publisher, 2026)
This research is intended to analyse the practice of tajdidun nikah as a reconciliation strategy and strengthening of marital commitment in Muslim families. This study is aimed to find the significance, function, and role of tajdidun nikah in restoring the relationship of husband and wife that experience domestic tension. The research in this study employs a qualitative method with a literature study methodology. Data were collected from Islamic law literature, Muslim family studies, journal papers and other relevant academic resources. The analysis was undertaken utilising the descriptive-analytical technique by examining the idea of tajdidun nikah from the standpoint of Islamic marital jurisprudence and family social dynamics. The findings indicate that tajdidun nikah is not only seen as a symbolic renewal of the marriage contract but also as a reflective place for couples to enhance their communication, increase their responsibilities, and restore their marital commitment. When done with the right religious knowledge, awareness of each other and the aim of preserving the unity of the family, this activity can be a form of reconciliation. However tajdidun nikah is not a substitute for resolving substantive home difficulties. Therefore, this practice needs to be supported by discourse, family guidance and commitment to behavioural change in order to foster the establishment of a harmonious, stable and sustainable family of Muslims.